2020
DOI: 10.1097/sla.0000000000002998
|View full text |Cite
|
Sign up to set email alerts
|

The Strain Ratio as Obtained by Endoscopic Ultrasonography Elastography Correlates With the Stroma Proportion and the Prognosis of Local Pancreatic Cancer

Abstract: A high SR as obtained by endoscopic ultrasonography elastography was associated with poor prognosis of resected pancreatic cancer but predicted improved survival for LAPC patients treated with the nab-paclitaxel and gemcitabine regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 22 publications
1
33
0
Order By: Relevance
“…Tumor stroma is a key component of pancreatic cancer. An increase in stroma reduces the efficacy of chemotherapy drugs (21). The present study showed that the expression of CTHRC1, a stroma related protein, was higher in the hypodense group.…”
Section: Discussionsupporting
confidence: 51%
“…Tumor stroma is a key component of pancreatic cancer. An increase in stroma reduces the efficacy of chemotherapy drugs (21). The present study showed that the expression of CTHRC1, a stroma related protein, was higher in the hypodense group.…”
Section: Discussionsupporting
confidence: 51%
“…Probably tumors with high stromal component are characteristic by hardness, so the surgeons tended to resect more pancreatic tissue to achieve a negative margin. However, no consensus has been reached on the prognostic impact of stromal component in patients with PDAC based on previous studies (7)(8)(9). We also found that TSR categories could be a strong and independent prognostic factor in patients with PDAC and demonstrated that the prognostic impact of TSR was almost similar with tumor grade and perineural invasion, which are regularly included in pathological reports.…”
Section: Discussionmentioning
confidence: 55%
“…Nevertheless, there exist some discrepancies in the prognostic impact of TSR in patients with PDAC. Using Masson trichrome staining or α-smooth muscle actin (α-SMA) staining in surgical specimen sections to evaluate stromal proportion, Shi et al reported that a stromal proportion of ≤60% was of benefit for prognosis in PDAC (7). Heid et al demonstrated that low tumor cellularity with a cutoff value of 30%, which was equivalent to a high amount of stroma, indicated better prognosis (8).…”
Section: Introductionmentioning
confidence: 99%
“…The TME, the 'soil' of tumor growth, is composed of cancer cells and various interstitial cells, including the extracellular matrix, proteolytic enzymes, cytokines and chemokines, and interacts with tumors by altering the proteome and degradome (8)(9)(10). As a prominent member of the stroma and as the most stromal or interstitial cells in the TME, CAFs have their own gene expression profiles that are different from NFs, and interact with cancer cells via a variety of signals to affect the TME, tumorigenesis, development and therapeutic tolerance of cancer cells (11)(12)(13), which are also associated with the prognosis of various tumors by expressing FAP, FGF-2, IL-1β-IRAK4 and Podoplanin (15,16,(40)(41)(42)(43)(44). Notably, the presence of reactive stroma in the TME, particularly in CAFs, was revealed to affect the tumor treatment effectiveness and was associated with tumor drug resistance (17)(18)(19)(20).…”
Section: Univariate Analysis Multivariate Analysis ------------------mentioning
confidence: 99%
“…Recent studies have demonstrated the critical role of CAFs in cancer stroma for tumorigenesis, development and the targeted therapy of cancers (8)(9)(10). In addition, tumor treatment effectiveness is complicated by the presence of reactive stroma in the Upregulated NOX1 expression in gallbladder cancer-associated fibroblasts predicts a poor prognosis TME, which is associated with tumor invasiveness and drug resistance (10)(11)(12)(13). CAFs have their own gene expression profiles that are different from normal fibroblasts (NFs), and they interact with cancer cells via a variety of signals in a paracrine or autocrine manner to affect the TME, determine cancer cell growth, invasion, metastasis, angiogenesis and therapeutic tolerance (14)(15)(16)(17), and predict the poor prognosis of patients (18,19).…”
Section: Introductionmentioning
confidence: 99%